A hybrid-fuzzy model with reliability-based criteria for selecting consumables used in welding dissimilar aluminum alloys joint - Aikhuele, Daniel (Engineering and Applied Science Research, 2019)
This study proposes a new MCDM model for the selection of the consumables (filler alloys) used in the welding of dissimilar aluminum alloy joints. The model is based on the triangular intuitionistic fuzzy hamming distance (TIFHD) and the induced triangular intuitionistic fuzzy ordered weighted geometric (I-TIFOWG) operator. It uses a value-index method to rank filler alloy alternatives and for determining the degree of flexibility in the decision-making process. The model has the following advantages: (1) the ability to capture fuzziness in the decision-making process, (2) it accounts for a degree of flexibility in the decision-making process, and, finally, (3) the method helps in reducing uncertainty in the evaluation process using the Triangular Intuitionistic Fuzzy Number(s). This allows for a more holistic and better tool for representing vague or imprecise information. In demonstrating the feasibility of the proposed model, a comparison analysis was performed. From the result of this analysis, it was observed that the model is feasible, flexible and accounts for the fuzziness in the decision-making process, as well as selecting the best filler alloy for a dissimilar aluminum weld.